Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO